DATA MINING TOOLS FOR STUDYING THE COMPETITIVE ENVIRONMENTDURING ENTERPRISE RELOCATION - MIKHALEVSKYI, VITALII; SKRYPNYK, TETIANA; VOZNIUK, LEONID; MEDVEDCHUK, VITALIY (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article considers a method for studying the competitive environment for enterprise relocation using data mining. The essence of the method is to optimize the process of studying the production environment for the possibility of enterprise relocation. By using this algorithm, human, production, financial resources and transport are distributed optimally for the most effective relocation of the enterprise. The current and potential risks and benefits for the new enterprise, logistical aspects and communication strategies are also described, which allows users to make informed decisions regarding enterprise relocation. The use of intelligent data analysis for studying the competitive environment and enterprise relocation includes a combination of forecasting, geographical analysis, modeling, multi-criteria decision-making methods and decision support through intelligent systems. These approaches allow businesses to effectively assess risks, opportunities, and optimal strategies for relocation, minimizing costs and increasing competitiveness in a new market. The concept of competitive environment research is considered and described in detail, the main task of this method and the objects used in the method are determined. A scheme of the method of studying the competitive environment for enterprise relocation is created. Factors that affect the effectiveness of the method are described. An information model of the method of studying the competitive environment for enterprise relocation using data mining tools is created, the technology of data preparation and the method of assessing the effectiveness of the study are described. The use of data mining tools for studying the competitive environment during enterprise relocation allows obtaining valuable information that can be used to make informed decisions. Systems of analysis, data collection, machine learning, and geoanalytics help to form a holistic view of the market, competitors, and consumer behavior, which ultimately contributes to the success of relocation.